A Comparison of Autogenous Cortico-Cancellous Bone Graft Obtained from the Wing of the Ilium with an Acetabular Reamer to Autogenous Cancellous Bone Graft Obtained from the Proximal Humerus in Dogs - Stallings, J. T.; Parker, R. B.; Lewis, D. D.; Wronski, Th. J.; Shiroma, J. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The incorporation of autogenous cortico-cancellous bone graft (CCBG) harvested from the wing of ilium using a powered acetabular reamer and autogenous cancellous bone graft (CBG), harvested from the proximal humerus by curettage, were compared in four young adult mixed breed female dogs. Five milliliters of CCBG or CBG were placed in bilateral, stable, 3.0 cm proximal diaphyseal ulnar defects. Humeral donor sites, and subsequent assignment of graft types of ulnar recipient sites, were alternated between dogs. Craniocaudal and lateral view radiographs were obtained immediately (day 0) and on days 16 and 35 after the operation. Photodensitometric and bone graft area measurements were made from these radiographs and the specific radiographic characteristics of the bone grafts were described at each time interval. Each dog received a series of intravenous fluorochrome label injections on days 23, 28 and 33. The dogs were humanely euthanatized on day 35. The bone graft recipient sites were harvested, processed and the descriptive histological and histomorphometric parameters were evaluated.A statistically significant difference in photodensitometric measurements was not seen between the CCBG and CBG. However, there was a statistically significant increase in the graft area of the CCBG from day 0-16. Mineral apposition rate was significantly greater, (P = 0.005) for the CCBG (mean = 4.8) than for the CBG (mean = 3.7), suggesting that the CCBG appears to be in an earlier more osteogenic phase of incorporation than the CBG. There was a trend which suggested that the percentage of trabecular bone volume was greater (P = 0.11) for the CBG (mean = 43.0) than for the CCBG (mean = 32.0). Other significant differences were not found, with respect to the other morphometric parameters measured. The descriptive histology and subjective radiographic evaluation were the most effective ways of readily distinguishing between the two types of bone graft and they demonstrated that the CBG had incorporated more completely than the CCBG by day 35.Presented at the 30th Annual Meeting of the American College of Veterinary Surgeons, Chicago, Illinois 1995 and at the 23rd Annual Meeting of the Veterinary Orthopaedic Society, Telluride, Colorado 1996
Keywords: Reamed cortico-cancellous bone graft; ilium